Pengaruh Kualitas Pelayanan Koperasi Tani Dewi Sri dan Produktivitas Kerja Petani terhadap Kesejahteraan Petani Di Subak Sengempel, Desa Bongkasa, Kecamatan Abiansemal, Kabupaten Badung - I Made Agus Wilantara; Ketut Suamba; I Gede Setiawan Adi Putra (Universitas Udayana, 2017)
ABSTRACTThe Influence of Service Quality of Dewi Sri Farmer’s Cooperative and theFarmer’s Work Productivity on the Welfare of Farmer’s at the Subak ofSengempel, Bongkasa Village, Sub-District of Abiansemal, Badung RegencyFarmer’s cooperative as a facilitator in improving welfare, the quality ofservice would be an important part in order to always be the selection of farmers toobtain the required product. The farmer’s cooperative is expected to provide the bestservices in order to achieve the welfare of farmers. An improved labor productivity offarmers as a source of income will have implications for the welfare of farmers. Thestudy objective was to determine the effect of service quality of the farmer’scooperative on the welfare of farmers at Subak of Sengempel.The research method used descriptive qualitative method. Total respondentswas 151 members of farmer’s cooperative taken by proportional random sampling.Data were analyzed using inferential statistics (SEM-PLS).The results showed that the quality of service of the farmer’s cooperative andthe farmer’s work productivity positively and very significantly effect on the welfareof farmers. Quality of services of the farmer’s cooperative positively and verysignificantly effect on the productivity of farmers. Quality of services of the farmer’scooperative has an influence in reaching the welfare of farmers, both directly andthrough the work productivity of farmers. The farmer’s cooperative should furtherimprove its reliability by serving members on time. The farmers of the Subak ofSengempel should increase the labor productivity by increasing the quantity of labor,especially by increasing the number of main harvests. The Local Government throughthe relevant departments should further improve coaching, training and monitoringof the services of the farmer’s cooperative and improving agricultural extensionprograms.Keywords: service, productivity, farmers, welfare.